Panduratin A, a possible inhibitor in metastasized A549 cells through inhibition of NF-Kappa B Translocation and chemoinvasion - Cheah, Shiau Chuen; Lai, Siew Li; Lee, Sui Ting; A. Hadi, A. Hamid; Mustafa, Mohd Rais (2013)
In the present study, we investigated the effects of panduratin A (PA), isolated from Boesenbergia rotunda, on apoptosis and chemoinvasion in A549 human non-small cell lung cancer cells. Activation of the executioner procaspase-3 by PA was found to be dose-dependent. Caspase-3 activity was significantly elevated at the 5 Âµg/mL level of PA treatment and progressed to a maximal level. However, no significant elevated level was detected on procaspase-8. These findings suggest that PA activated caspase-3 but not caspase-8. Numerous nuclei of PA treated A549 cells stained brightly by anti-cleaved PARP antibody through High Content Screening. This result further confirmed that PA induced apoptotic cell death was mediated through activation of caspase-3 and eventually led to PARP cleavage. Treatment of A549 cells with PA resulted in a strong inhibition of NF-ÎºB activation, which was consistent with a decrease in nuclear levels of NF-ÎºB/p65 and NF-ÎºB/p50 and the elevation of p53 and p21. Besides that, we also showed that PA significantly inhibited the invasion of A549 cells in a dose-dependent manner through reducing the secretion of MMP-2 of A549 cells gelatin zymography assay. Our findings not only provide the effects of PA, but may also be important in the design of therapeutic protocols that involve targeting of either p53 or NF-ÎºB.